Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement

Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor